Hepatocellular Carcinoma: An Uncommon Metastasis in the Orbit - Maria-Nikoletta Protopapa; Maria Lagadinou; Theodoros Papagiannis; Charalambos A. Gogos; Elena E. Solomou (Case Reports in Oncological Medicine)
Hepatocellular carcinoma (HCC) represents the most common type of primary cancer of the liver and is associated with poor prognosis. It is the most common cause of death in cirrhotic patients and in different studies was shown as the third most common cause of cancer-related deaths worldwide. Each year, approximately half a million people are diagnosed with HCC. In recent decades, the prognosis of patients with HCC has improved because more cases are diagnosed and treated at early stages; high-risk patients (i.e., with chronic HBV or HCV infection) are followed more often for the possibility of HCC, and novel treatment options such as locoregional therapy are used with better overall results. The extrahepatic metastases represent a poor prognostic factor. The most common sites of metastasis in advanced hepatocellular carcinoma are the lung (44%), portal vein (35%), and portal lymph nodes (27%). Also, intra-abdominal lymph nodes and bones are common sites. Orbital metastases rarely occur, representing the 3-7% of orbital masses. These metastases are usually found in advanced tumor stages. The mechanism of metastasis to the orbit is difficult to determine. A hematogenous route, as for other primary neoplasms of the abdomen, may be suspected. Tumor cells may circulate through the vena cava, beyond the pulmonary filter to the heart, and finally be distributed to the orbital region through the arterial systemic circulation. We describe herein a case of an adult male with liver cirrhosis due to alcohol abuse who presented with concomitant diagnosis of HCC and orbit metastasis.